A formação ética dos adolescentes - Souza, Andréia Dutra de (2007)
The main objective in this dissertation was lived for and reflects about didactic situation, study dynamic of ethics and social values. It was developed reflective activities about: relationships among parents and children, betroth, sexuality, drugs, prejudice and violence. The research has been developed through the qualitative approach. The study carried out on the intervention, show that, researcher and participants of research are historic and contextualized people, they are both elements of scientific do. In order to develop the research, it was created in the classroom, situations of participation, discussion and dialogue about subjects that have relation with ethic. This dissertation is justified by its methodology which intend identify opinions and attitudes to be taken in each fact related in the classes, in face to the cultural and social diversity. The data was collect in a school in Presidente Prudente SP, with one hundred and ten adolescents: sixty one boys and forty nine girls, between the ages of 13 and 16. The findings show us that young people need dialogue and orientation, they seem to be lost in their attitudes and how they are developing the opinion formation process, the dialogue with their parents is important.